2021
DOI: 10.36418/jiss.v2i7.365
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Profesionalisme, Pengalaman dan Etika Terhadap Kualitas Audit

Abstract: MEA atau kita kenal dengan istilah Masyarakat Ekonomi Asean slah satu pemicu utama perkembangan ekonomi Indonesia. Kebijakan untuk mengwasi perkembangan ini adalah dengan pemeriksaan oleh pihak ketiga yaitu auditor eksternal. Tujuan penulisan artikel ini untuk memperoleh bukti empiris antara profesionalisme, pengalaman kerja, dan etika profesi terhadap kualitas audit seorang auditor. KAP wilayah Denpasar menjadi objek penelitian dalam artikel ini. Sampel ditentukan dengan purposive sampling. Hasil penelitian m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 1 publication
0
3
0
2
Order By: Relevance
“…An auditor In auditing the annual financial statements, one must not only carry out a code of ethics properly so that the resulting audit quality will be good. This research is not in line with the research of Rengganis & Mirayani (2021), Kirana (2021), andYuli et al (2019) their research shows that an auditor in auditing annual financial reports must carry out a regulated code of ethics so that the resulting audit quality will be good. Effect of audit quality in moderating accountability on auditor performance concluded that the audit quality variable moderates the accountability relationship.…”
Section: Results Andʿdiscussionmentioning
confidence: 58%
See 1 more Smart Citation
“…An auditor In auditing the annual financial statements, one must not only carry out a code of ethics properly so that the resulting audit quality will be good. This research is not in line with the research of Rengganis & Mirayani (2021), Kirana (2021), andYuli et al (2019) their research shows that an auditor in auditing annual financial reports must carry out a regulated code of ethics so that the resulting audit quality will be good. Effect of audit quality in moderating accountability on auditor performance concluded that the audit quality variable moderates the accountability relationship.…”
Section: Results Andʿdiscussionmentioning
confidence: 58%
“…De Angelo (1981) put more emphasis on contextual audit quality (Ardianingsih, 2018:23). The relationship between audit quality and professional ethics on auditor performance refers to research by Rengganis & Mirayani (2021), Kirana (2021), andYuli et al (2019), in his research shows an auditor in auditing annual financial reports must carry out a code of ethics that has been regulated so that the resulting audit quality will be good. H4: Audit quality moderates professional ethics on auditor performance Auditors are required to be responsible for their profession, prioritize the interests of the community, have a responsibility professional, have high integrity, be objective in work, impartial to the interests of anyone, and always develop their abilities to improve expertise and quality of services provided.…”
Section: Theoretical Framework and Hypothesis Developmentmentioning
confidence: 99%
“…Variabel Mediasi, Ghema Purnama Sari dan Ni Ketut Rasmini merupakan salah satu unsur untuk melihat sejauh mana auditor tersebut bersikap profesional, karena pengetahuan dan keahlian seorang auditor dibangun dari seberapa lama pengalamannya menjadi seorang auditor (Rengganis & Mirayani, 2021). Menurut Pandoyo (2016), pengalaman dapat diperoleh oleh auditor dengan melakukan penugasan audit dan jika proses pemantauan berjalan dengan baik.…”
Section: Pengaruh Pengalaman Auditor Dan Audit Capacity Stress Pada K...unclassified
“…Berdasarkan uraian tersebut, maka hipotesis yang dapat diajukan adalah sebagai berikut. H2: Audit capacity stress berpengaruh positif pada kompetensi Pengalaman auditor merupakan salah satu unsur melihat sejauh mana auditor tersebut bersikap profesional, karena pengetahuan dan keahlian seorang auditor dibangun dari seberapa lama pengalamannya menjadi seorang auditor (Rengganis & Mirayani, 2021). Seiring dengan meningkatnya pengetahuan dan kemampuan yang dimiliki seorang auditor baik dalam segala bidang pendidikan, hal ini juga akan meningkatkan kualitas audit yang dihasilkannya (Sarca & Rasmini, 2019).…”
Section: Pengaruh Pengalaman Auditor Dan Audit Capacity Stress Pada K...unclassified
“…Starting from its first publication in 1978 until the latest in 2017, the IPPF has been changed several times (BERNAWATI, 2020) Audit quality includes all aspects that are considered so that the independent auditor's report is quality. Independent auditors must comply with several principles: professional responsibility, responsible for the public interest, honest, objective, maintaining competence, protecting auditor secrets, behaving professionally, and working in accordance with technical standards (Mirayani, 2022) Apart from having expertise in the field of accounting, accountants must act professionally according to the ethics of audit professionalism. Acting in this way will increase company and public confidence in the accounting profession (R. A.…”
Section: Introductionmentioning
confidence: 99%